Effect of Weed Control on the Growth of Populus deltoides G3 at Nursery Stage - Singh, Jagdish; Dhiman, R. C. (Indian Forester, 1999)
Weed control program has considerably enhanced the growth of Populus deltoides G3 at the nursery stage. Though T4 (manual weeding), was the best method to control weed, but it is labour intensive and costly. T2 - (Glyphosate-4 application), at the rate of 5 ml diluted in 1 litre of water was also found equally good; thus it is recommended where there is labour scarcity.